Higher education in the Asia-Pacific : strategic responses to globalization - Marginson, Simon (Springer, 2015)
This survey provides unprecedented scope and detail of analysis on higher education in the Asia-Pacific region. In this era of global integration, convergence and comparison, the balance of power in worldwide higher education is shifting. In less than two decades the Asia-Pacific region has come to possess the largest and fastest growing higher education sector on Earth. The countries of East and Southeast Asia and the Western Pacific together enrol 50 million tertiary students, compared to 14 million in 1991, and will soon conduct a third of all research and development. In China, Hong Kong, Taiwan, Korea and Singapore, u2018world-classu2019 universities are emerging at breakneck pace, fostered by modernizing governments that see knowledge and skills as key to a future shaped equally by East and West, and supported by families deeply committed to education. But not all Asia-Pacific countries are on this path, not all reforms are effective, and there are marked differences between nations in levels of resources, educational participation, research, state controls and academic freedom. Higher Education in the Asia-Pacific: Strategic responses to globalization provides an authoritative survey of tertiary education in this diverse and dynamic region. Its 23 chapters, written by authors from a dozen different countries, focus successively on the Asia-Pacific as a whole, the strategies of individual universities, and national policies and strategies in response to the global challenge.